Can rural elderly groups be supported by increasing the pension contribution rate? - Haibo Lin; Yihan Xu; Yueming Song (Heliyon)
As a typical East Asian country transitioning from a production-based social insurance system to a modern free social insurance system, South Korea has set a precedent for other Asian countries. This study adopts data from 2006, 2010, and 2012 Korean Longitudinal Study of Aging (KLoSA) and uses a fixed effect analysis of the quasi-natural experiment to conclude that the increase in the Korean pension contribution rate has a limited negative impact on social security participation. The degree of filial piety of children, including the financial support of those children, rather than the number of children, affects the participation of the elderly in social security insurance. Thus, an alternative relationship between family pensions and social pensions presents itself. This paper discusses the mechanism that factors influence the willingness to participate in pension insurance with reduced replacement rates in an extended family of a multigenerational population. After systematically delineating the background of South Korea's welfare system, this paper compares the similarities between China and South Korea in this regard and proposes that China and other East and Southeast Asian countries can learn from South Korea's example.